Criteria for radionuclide activity concentrations for food and drinking water (IAEA-TECDOC ;, 2016)
"This publication considers the various international standards to be applied at the national level for the assessment of levels of radionuclides in food and in drinking water in different circumstances for the purposes of control, other than in a nuclear or radiological emergency. It collates and provides an overview of the different criteria used in assessing and controlling the radionuclide content of food and drinking water. The approach used to derive reference levels of radionuclide activity concentration in food and in drinking water as criteria for use in particular circumstances is also considered. This publication is intended for the use by regulatory bodies, policy makers and interested parties with responsibilities in relation to the management of various situations where radionuclides are, or could be, present in food and in drinking water, other than in a nuclear or radiological emergency."--Publisher's description.